Promyelocytic leukemia (PML) protein plays important roles in regulating cell adhesion, morphology, proliferation and migration. - Mei Kuen Tang (Public Library of Science (PLoS), 2013)
PML protein plays important roles in regulating cellular homeostasis. It forms PML nuclear bodies (PML-NBs) that act like nuclear relay stations and participate in many cellular functions. In this study, we have examined the proteome of mouse embryonic fibroblasts (MEFs) derived from normal (PML(+/+)) and PML knockout (PML(-/-)) mice. The aim was to identify proteins that were differentially expressed when MEFs were incapable of producing PML. Using comparative proteomics, total protein were extracted from PML(-/-) and PML(+/+) MEFs, resolved by two dimensional electrophoresis (2-DE) gels and the differentially expressed proteins identified by LC-ESI-MS/MS. Nine proteins (PML, NDRG1, CACYBP, CFL1, RSU1, TRIO, CTRO, ANXA4 and UBE2M) were determined to be down-regulated in PML(-/-) MEFs. In contrast, ten proteins (CIAPIN1, FAM50A, SUMO2 HSPB1 NSFL1C, PCBP2, YWHAG, STMN1, TPD52L2 and PDAP1) were found up-regulated. Many of these differentially expressed proteins play crucial roles in cell adhesion, migration, morphology and cytokinesis. The protein profiles explain why PML(-/-) and PML(+/+) MEFs were morphologically different. In addition, we demonstrated PML(-/-) MEFs were less adhesive, proliferated more extensively and migrated significantly slower than PML(+/+) MEFs. NDRG1, a protein that was down-regulated in PML(-/-) MEFs, was selected for further investigation. We determined that silencing NDRG1expression in PML(+/+) MEFs increased cell proliferation and inhibited PML expression. Since NDRG expression was suppressed in PML(-/-) MEFs, this may explain why these cells proliferate more extensively than PML(+/+) MEFs. Furthermore, silencing NDRG1expression also impaired TGF-β1 signaling by inhibiting SMAD3 phosphorylation.